The Study of the Design Process for Development and Conservation of China Town District: A Case Study of Weangnakonkasem Community - Luechajarassin, Prachaya (Journal of Architectural/Planning Research and Studies (JARS), 2014)
The development of public transportation in urban areas to the rail system and the construction project of subway through the center of Bangkok have created an adverse impact to Chinatown, the old commercial areas of Bangkok. Weangnakonkasem Community is one of the examples of the areas receiving the impact. The construction of MRT-blue line through Wang Burapha areas caused the landlord to have an idea to sell the land in Weangnakonkasem since the area is within 500 m from the MRT station, and so receive an encouragement for intense economic development. This idea caused the conflict between landlord and leaseholders living in Weangnakonkasem since this area is an old commercial area where Chinese people have settled down and inhabited for at least four generations. To conserve the place where their ancestors have started and pass on their culture to the next generation, the inhabitants in Weangnakonkasem have aggregated the money and requested to buy the land from the landlord, and discussed within the community to find the way to develop the land. This research is an action research having an objective to study the design procedure for land development that can retain the cultural value of Weangnakonkasem Community using participatory process. The researcher used culture, study visit and knowledge exchange as the tools to work with the community. The project started by brainstorming the ideas from community, aggregating information, analyzing the problems, finding the solution which finally leading to the procedure for land development design. However, while researcher was working together with Weangnakonkasem Community, the land has been sold to the new landlord. Consequently, the land development plan of Weangnakonkasem Community needed to be stopped without a chance to achieve the objective. The researcher had a chance to present the initial development design to the community, listen to their opinions and obtain a conclusion. The important issues toward the development and conservation of Weangnakonkasem Community that have been found are: (1) the identity and the importance of old town community toward the spirit of the city; (2) the important factors for the success of the project, and (3) the important process and project procedure that can lead to the success of the project.